Analisis Penerapan Storytelling sebagai Metode Pembelajaran pada Mata Kuliah Digital Storytelling Mahasiswa Komunikasi IPB 61 - Erinna Aulia Rifay; Amiruddin Saleh; Harvia Atika Zahira (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The storytelling method is increasingly relevant for higher education, particularly in communication-oriented study programs within the digital era. This study examines the application of storytelling as a teaching method in the "Digital Storytelling" course for the Class of 61 students in the Digital Communication and Media Study Program at the Vocational School, IPB University. A descriptive qualitative approach was employed, utilizing in-depth interviews with the course instructor and students from four different classes. The results indicate that storytelling was implemented through opening narratives, case study presentations, the sharing of real-life experiences, and interactive discussions that fostered student participation. Findings also reveal that students perceived the method as an approach that helped link concepts to daily experiences, facilitated the understanding of course material, improved skills in structuring messages, fostered creativity in crafting digital narratives, and boosted confidence in conveying ideas. Consequently, storytelling is viewed as a teaching method capable of supporting a more meaningful, contextual, and participatory learning experience in digital communication education.